Knowledge driven strategy formulation process to sustain large family-based businesses - Binladen, Hania Saleh (Cranfield University, 2017)
This thesis aims to develop a knowledge-driven strategy formulation framework for large family-based businesses in the Gulf Cooperation Council countries, to help them remain sustainable and able to deal with future external changes. Its objectives were 1) to capture best practice in the literature on developing strategies for ensuring long-term competitive advantage by promptly addressing external changes; 2) to identify the prominent factors of enterprise strategy using a literature review and industry-based case study; 3) on this basis, to develop a platform; 4) to define the knowledge-driven processes that support strategy formulation for the target businesses. Thus, the literature informs the framework and its elements, based on best practices. In parallel, 15 GCC case studies provided data on the activities, tools and influential factors affecting the strategic decisions of the strategy formulation team. In each case, CEOs and strategic managers were interviewed and corporate websites and other secondary data were analysed. The research deliverables were validated through case study methodology and evaluated by 8 experts in strategy formulation. The key contributions to knowledge are 1) development of a strategy formulation process based on best practices; 2) creation of an instance of modelling the strategy formulation process, using IDEF0, to show the interactions and interrelationships between decision making and decision support activities; 3) construction of an influential factor model to show which influential factors are written in which reports and how they influence different decisions; 4) development of a strategy formulation team model to understand the different roles and functions of the strategy formulation team members; 5) creation of a new taxonomy of the strategic tools proposed to strategy formulation teams for enhancing the process of collecting, analysing and reporting the knowledge of influential factors. The implications of this research are that 1) strategy formulation processes are not linear but systematic and iterative and thus can enhance the flow of information and decisions; 2) the existence of different members in the strategy formulation process enriches the decision making and decision support activities, since each has a specific role and function; 3) different report based influential factors are required in different decisions. However, the implicit preferences in understanding these influential factors are critical for decision-making.